RNF31 induces paclitaxel resistance by sustaining ALYREF cytoplasmic–nuclear shuttling in human triple‐negative breast cancer - Shumei Huang; Dongni Shi; Shuqin Dai; Xingyu Jiang; Rui Wang; Muwen Yang; Boyu Chen; Xuwei Chen; Lingzhi Kong; Lixin He; Pinwei Deng; Xiangfu Chen; et al. (Clinical and Translational Medicine, 2025)
Abstract Background Resistance to paclitaxel‐based chemotherapy is the major obstacle in triple‐negative breast cancer (TNBC) treatment. However, overcoming paclitaxel resistance remains an unsolved problem. The present study aimed to determine whether paclitaxel treatment impairs Aly/REF export factor (ALYREF) cytoplasmic–nuclear shuttling, its mechanism, and the role of ubiquitinated ALYREF in paclitaxel resistance. Methods The subcellular proportion of ALYREF was detected in samples from patients with TNBC using immunohistochemistry to analyze the relationship between ALYREF distribution and paclitaxel response. Cell viability assays, immunofluorescence assays, quantitative real‐time reverse transcription PCR assays, western blotting, and terminal deoxynucleotidyl transferase nick‐end‐labelling assays were conducted to measure the biological function of the subcellular proportion of ALYREF and E3 ligase ring finger protein 31 (RNF31) on paclitaxel sensitivity in TNBC. The synergistic effects of an RNF31 inhibitor plus paclitaxel on TNBC were evaluated. Cox regression models were adopted to assess the prognostic role of RNF31 in TNBC. Results Herein, we showed that regulation of ALYREF cytoplasmic–nuclear shuttling is associated with the paclitaxel response in TNBC. In paclitaxel‐sensitive TNBC, ALYREF was trapped in the cytoplasm by paclitaxel, while in paclitaxel‐resistant TNBC, ALYREF was efficiently transported into the nucleus to exert its function, allowing the export of the mRNAs encoding paclitaxel‐resistance‐related factors, including tubulin beta 3 class III (TUBB3), stathmin 1 (STMN1), and microtubule‐associated protein Tau (TAU), ultimately inducing paclitaxel resistance in TNBC. Mechanistically, we found that RNF31 interacts with and ubiquitinates ALYREF, which facilitates ALYREF nuclear transportation via importin 13 (IPO13) under paclitaxel treatment. Notably, the RNF31 inhibitor and paclitaxel synergistically repressed tumour growth in vivo and in TNBC patient‐derived organoids. In addition, analysis of patients with TNBC showed that elevated RNF31 levels correlated with poor prognosis. Conclusion These data indicated that RNF31‐mediated ALYREF ubiquitylation could represent a potent target to reverse paclitaxel resistance in TNBC. Key points RNF31 facilitated ALYREF‐mediated PTX resistance in TNBC. RNF31 promoted ALYREF nuclear transport via IPO13 in response to PTX treatment, subsequently enhancing the export of mRNAs encoding PTX resistance‐related factors, including TUBB3, STMN1, and TAU. Blocking RNF31 trapped ALYREF in the cytoplasm and induced TNBC cell death upon PTX treatment. Inhibiting RNF31 activity re‐sensitized PTX‐resistant TNBC to PTX treatment.